Practical Salesforce development without code : building declarative solutions on the Salesforce platform - Weinmeister, Philip (Apress, 2019)
Use this hands-on guide to build powerful solutions on the Salesforce platform without using a single line of code. This revised and expanded second edition includes Process Builder, Flow Builder, Lightning App Builder, Lightning Bolt Solutions, and more. Practical Salesforce Development Without Code shows you how to unlock the power of the Salesforce platform to solve real business problems. Adhering to Salesforce's "clicks, not code" mantra, Salesforce expert Phil Weinmeister walks Salesforce newcomers and veterans through different business problems and identifies effective-and proven-approaches to solutions using the platform's declarative framework. By adopting this book as your guide, you will learn how to deliver business solutions within Salesforce by combining analysis, creativity, and logic with core elements such as validation rules, workflow rules, processes, flows, formula fields, and Lightning apps. In addition, Weinmeister dissects and explains the most useful functions and features for declarative developers and shows you how to use them. Best of all, Weinmeister uses real-life business scenarios and visuals. Applying the lessons learned from this how-to guide will ultimately save you time and ensure that your clients or internal customers are enabled, equipped, and empowered. What You'll Learn: Build objects, fields, and relationships to establish a sensible data model Automate business processes by using Workflow, Process Builder, and Flow Utilize functions and develop formulas effectively for a variety of business needs Develop approval processes to handle exception scenarios Employ actions to easily create efficient and relevant user experiences Manage your environments and deploy your solutions